TIZ 6938 - Final Project and Internal Industrial Internship - Dzul Majdi, Mohd Dashilah (College of Arts and Sciences, 2008)
The paper report on Talian Tulen Sdn. Bhd. The company is founded by UUM Master of Science Technopreneurship student. The report consist of company profile, business plan, sales achievement report, financial report, future plan and audit verification.